One-Pot Synthesis of Gelatin/Gum Arabic Hydrogels Embedding Silver Nanoparticles as Antibacterial Materials - Irina Popescu; Irina Mihaela Pelin; Irina Rosca; Marieta Constantin (Gels)
High and large-spectrum antibacterial features and ROS scavenging properties are the most important requirements for efficient wound-dressing materials. A composite hydrogel was synthesized herein by a one-pot procedure embedding silver nanoparticles (AgNPs) covered with oxidized gum arabic (OGA) within gelatin (Gel) hydrogel. Small (2–20 nm), round-shaped AgNPs (ζ = −22 mV) were first obtained by green synthesis using OGA as a reducing and capping agent. Composite hydrogels, containing 0.6 and 1.3 wt.% Ag, were obtained by the covalent cross-linking (Schiff base reaction) of amine groups in gelatin with the dialdehyde groups located on the shell of the AgNPs. Thus, the uniform distribution of the AgNPs in the network contributed to the increased physicochemical and hydrolytic stability of the hydrogels. Moreover, the high swelling degree together with the good mechanical properties make them appropriate candidates for wound-healing materials. The hydrogels exhibited 80% scavenging activity of ABTS●+ free radicals after 6 h of incubation and were effective against E. coli and S. aureus, achieving a 4% survival of bacteria within 3 h (E. coli) and 24 h (S. aureus). These results clearly indicate that the proposed hydrogels have potential in wound-dressing applications.